The Impact of CSR Activities on Brand Loyalty of Saudi High Street Banks - Mian, Tariq (مجلة العلوم الإدارية و الإقتصادية, 2020)
This paper aims to explore key concepts in relation to corporate social responsibility (economic, legal, ethical, and discretionary attributes) and the impact that the concept may have on consumer behaviour patterns, focusing specifically on brand loyalty of the Saudi (does this need to be capital?) high street bank. Data was collected by using the online survey. Convenience sampling technique was used to get the response from the respondents. 224 questionnaires were returned with the rate of 44% response. A PLS-SEM approach was employed to test the hypotheses. The results revealed that three attributes of the CSR namely legal, ethical, and discretionary attributes found, significantly correlated with the brand loyalty of the high street bank customers. However, one attribute, namely economic, was not found to be statistically significant. The results of this study suggest that the high street banks operating in the KSA should focus more on the CSR attributes, particularly, legal, ethical, and discretionary attributes which significantly affect the customer brand loyalty.